La promotion de l’excellence en éducation prioritaire à l’épreuve de la gouvernance par dispositif. Étude du déploiement des parcours d’excellence en France - Ariane Richard-Bossez; Renaud Cornand; Alice Pavie (Cahiers de la Recherche sur l'Education et les Savoirs, 2021)
This article examines French policies in the fight against educational inequalities using the example of a device promoting excellence deployed in Priority Education (pe) areas since 2016: the Parcours d’excellence (Pathways to Excellence). Based on a case study of a highly endowed academy in schools classified as pe, it offers an analysis based on the sociology of public action, focusing more particularly on the transformations of excellence that occur within the different levels of the implementation of this device. Three levels are questioned throughout the three parts of the article: the ministerial level and the progressive arrival of excellence systems in Priority Education; the academic level and the reconfigurations of excellence to which it gives rise; the level of the school establishments and the variety of appropriations of this system that can be observed there.